Gender Disparity in Publishing Six Months after the KITP Workshop Probes of Transport in Stars. (1st August 2022) - Joyce, Meridith; Tayar, Jamie; Lecoanet, Daniel
Abstract: Conferences and workshops shape scientific discourse. The Kavli Institute for Theoretical Physics (KITP) hosts long-term workshops to stimulate scientific collaboration that would not otherwise have taken place. One goal of KITP programs is to increase diversity in the next generation of scientists. In this analysis, we examine gender trends in the authorship of papers that have been generated as a result of the KITP program Probes of Transport in Stars, which ran from 2021 October 11th to 2021 December 17th. While 38% of workshop participants were women, only 19% of publications produced between 2021 December 1st and 2022 June 3rd had female first-authors. Furthermore, of these early publications, 61% had all-male author lists. Among publications resulting from the KITP program, the proportions of both male first-author papers and papers with all-male author lists are higher than predicted by models that take into account the gender distribution of the KITP participants. These results motivate more thorough investigations of collaboration networks at scientific conferences and workshops. Importantly, they also suggest that programs, conferences, and workshops of any kind need to take steps beyond those implemented in this KITP program to enable more diverse collaborations and address gender disparities in science.